Preference utilization in the global economy: An empirical analysis - Gianmarco Cariola; Rainer Lanz (World Trade Organization (WTO), 2022)
This paper analyses the determinants of preference utilization using a novel WTO dataset that allows us to measure the underutilization of preferences across several importers, exporters and products over time. Building on the previous literature, we confirm that preference utilization is increasing with the size of exports, preference margin and geographical and linguistic proximity. We find that utilization rates tend to be higher for reciprocal preferences compared to non-reciprocal preferences, and that the incentive to use preferences increases with the share of competitors' exports that is eligible for preferential treatment. Our most innovative contribution is the analysis of the relationship between preference utilization and the production structure of the countries that benefit from preferential market access. Using an instrumental variable approach, we show that an increase in value added reduces both underutilization and its sensitivity with respect to the preference margin, making the use of preferences more robust with respect to trade policy changes. Analogously, a change in the preference margin will have a differential impact on sectors depending on their value added content. We explain this finding by introducing the concept of "effective preference margin" to measure the importance of the benefits from preference utilization relative to the value added content of exports.
Keywords: F13; F14; F15; 330; trade policy; preference utilization; value added trade